Data Analytics to Improve Customer Energy Efficiency - Angelopoulos, Michail; Pollalis, Yannis (Archives of Business Research, 2021)
This research focuses on providing insights for a solution for collecting, storing, analyzing and visualizing data from customer energy consumption patterns. The data analysis part of our research provides the models for knowledge discovery that can be used to improve energy efficiency at both producer and consumer ends. Τhe study sets a new analytical framework for assessing the role of behavioral knowledge in energy efficiency using a wide range of Case Studies, Experiments, Research, Information and Communication Technologies (ICT) in combination with the most modern econometric methods and large analytical data taking into account the characteristics of the study participants (household energy customers).